Rotenone accelerates endogenous α-synuclein spreading and enhances neurodegeneration in an intra-striatal α-synuclein preformed fibril injected mouse model of Parkinson’s disease - Khan, Engila; Radwan, Nada; Ardah, Mustafa T.; Kitada, Tohru; Haque, M. Emdadul (Frontiers in Cellular Neuroscience, 2025)
Prominent histopathological features of Parkinson’s disease (PD) include the presence of Lewy bodies, intra-neural protein aggregates mainly composed of α-synuclein (α-syn), and cell death of dopaminergic neurons. Epidemiological studies have revealed a correlation between exposure to environmental neurotoxins, such as rotenone, and an increased risk of developing PD. In this study, we evaluated the role of rotenone in α-syn spreading and accumulation, with the aim of developing a mouse model of accelerated PD. Human α-synuclein pre-formed fibrils (PFF) were injected into the mouse striatum by stereotactic surgery. Rotenone (2.5 mg/kg-body-weight) was administered intraperitoneally once daily for four consecutive weeks one day or three weeks after the PFF injection. Brains were collected twenty-four hours after the last injection for immunohistochemical analysis. In this study, rotenone significantly synergized PFF induced α-syn spreading, neuroinflammation, in addition to augmented loss of dopaminergic neurons along the nigrostriatal pathway.